EFFECTIVENESS OF E-LEARNING FROM ISLAMIC PERSPECTIVES ON THE COVID-19 PANDEMIC: THE CASE STUDY AMONG UNDERGRADUATE IN MALAYSIA (International Journal of Islamic Business, 2023)
This research paper aims to study the effectiveness and to explore Islamic perspectives of e-Learning during the Covid-19 pandemic. It focuses on the undergraduate business students, who have used online learning as a part of their learning method. This study uses 118 undergraduate business students from different higher-learning institutions in Malaysia. Later, the analysis is conducted using descriptive and cross-tabulation analysis. The findings show that during the emergency e-Learning, many of the students indicated the ineffectiveness of e-Learning due to the factors of unable or slow internet access or connectivity, working in a limited space and constraints of adapting new environment of online learning. Apparently, findings are also showing that instructors have played a big role in ensuring the effectiveness of e-Learning during the Covid-19 pandemic with various online assessment methods. This study provides a finding on the effectiveness of e-Learning during the Covid-19 pandemic among business students in Malaysia. It offers some new insights related to the effectiveness of e-Learning and helps the relevant policymakers to offer an appropriate intervention strategy in optimizing e-Learning in the future.